Suplementasi β-glucan dari ragi roti (Saccharomyces cerevisiae) dalam pakan terhadap aktivitas fagositosis, aktivitas NBT, total protein plasma dan aktivitas aglutinasi darah ikan nila (Orechromis niloticus) - Sri Dwi Hastuti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Tilapia is an important fisheries comodity which intesively farmed in Indonesia. However, an intensive farming system of aquatic organism often lead to disease outbreak. Ones the disease emerged, it will be difficult to combat. The curing method by using antibiotics in aquatic organism will bring negative impacts, such as causing bacteria resistance and decline of aquatic environments. Therefore control of disease in aquatic organism should be done through preventive methods such as the use of β-glucan from baker’s yeast (Saccharomyces cerevisiae). It is widely known that yeast’ cell wall contain of immunostimulant substance namely β-glucan. This research was aimed to find the effect of different dose of β-glucan in diet toward the phagocytic activity, respiratory burst which is indicated by Nitroblue Tetrazolium (NBT) activity, total of protein plasm and agglutination activity of tilapia blood. Method used in this study was experiment by complete random design using five treatments triplicate. Those treatments were β-glucan 0; 2,5; 5; 7,5 and 10 ppmkg-1 diet. Result showed that the different dose of β-glucan in diet gave a significantly effect on the phagocytic activity and total of protein plasm, but not on respiratory burst (NBT activity). The highest phagocytic activity occured in treatment E (β-glucan 10 ppmkg-1 diet) with the value of phagocytic activity was 37,67%, whereas the highest of total of protein plasm was occured in treatment B (β-glucan 2,5 ppmkg-1 diet) with the value of 123,58 mgml-1. Keywords : Baker’s yeast, β-glucan, phagocytic and agglutination activity, NBT activity, total of protein plasm